1998
DOI: 10.1111/j.1471-6402.1998.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Male and Female College Students' Experiences of Sexual Coercion

Abstract: Research comparing men's and women's experiences of sexual coercion has typically assessed differences in prevalence rates and risk. We extended this line of research by comparing the contexts of sexual coercion and reactions to sexually coercive experiences in an attempt to understand the meanings that men and women attribute to these events. Participants were 433 randomly selected college students who responded to an anonymous survey. In line with past research, more men than women reported being sexually co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
121
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 30 publications
(33 reference statements)
16
121
1
Order By: Relevance
“…Also, because contextual factors, such as relationship status, were not considered in the present study, it cannot be assumed that the behavioral tactics employed were equivalent in meaning and impact. Research indicates that men are generally more accepting of sexual advances than women (Black & Gold, 2003) and may have a wider range of emotional responses to experiences of sexual coercion with the opposite sex (Anderson & StruckmanJohnson, 1998;O'Sullivan, Byers, & Finkelman, 1998). Furthermore, we found that, although more men than women reported obtaining or trying to obtain sex play or oral sex through coercive means, roughly equal percentages of both groups reported obtaining or trying to obtain vaginal or anal intercourse.…”
Section: Prevalence Of Sexual Coercion Across Gendermentioning
confidence: 99%
“…Also, because contextual factors, such as relationship status, were not considered in the present study, it cannot be assumed that the behavioral tactics employed were equivalent in meaning and impact. Research indicates that men are generally more accepting of sexual advances than women (Black & Gold, 2003) and may have a wider range of emotional responses to experiences of sexual coercion with the opposite sex (Anderson & StruckmanJohnson, 1998;O'Sullivan, Byers, & Finkelman, 1998). Furthermore, we found that, although more men than women reported obtaining or trying to obtain sex play or oral sex through coercive means, roughly equal percentages of both groups reported obtaining or trying to obtain vaginal or anal intercourse.…”
Section: Prevalence Of Sexual Coercion Across Gendermentioning
confidence: 99%
“…Of this sample, 34% of females had been victims of sexual coercion by their partners (Basile, 2002). O'Sullivan, Byers, and Finkelman (1998) examined the prevalence of SC by sending anonymous questionnaires to a random sample of university students. Their final sample size comprised 346 never-married students (216 women and 130 men).…”
Section: Introductionmentioning
confidence: 99%
“…Verbal coercion was selected because it is the most commonly employed tactic by both men and women and occurs frequently enough in a U.S. college sample to allow comparison (Muehlenhard and Cook 1988;O'Sullivan et al 1998;Russell and Oswald 2002;Struckman-Johnson and Struckman-Johnson 1998). Since sexual refusal often occurs in a situation that is emotionally and physically charged, it can evoke a strong negative affect and response from one or both partners.…”
Section: Introductionmentioning
confidence: 99%